PENGGUNAAN CLOUD COMPUTING DALAM PERANCANGAN APLIKASI MOBILE BERKONSEP GAMIFIKASI BERKEBUN - Korbafo, Adrianus Ragil Indrajaya; Nababan, Darsono; Risald, Risald (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
Climate change causes an increase in global temperature, which results in rising sea levels and threatens many cities in the future, including Jakarta. Carbon emissions are the primary cause of climate change, which is difficult to reduce. Forests can act as a natural filter for carbon emissions, but deforestation still occurs for various reasons. The author and their team propose a solution by creating an application called "Eden" that uses gamification to encourage users to develop a habit of planting trees. This application encourages the public to participate in saving the earth from global warming and climate change by planting trees around their homes, which can filter some of the carbon emissions in their environment.